Asymmetric Synthesis of Hydroquinolines with α,α‐Disubstitution through Organocatalyzed Kinetic Resolution - Chen, Yunrong; Zhu, Chaofan; Guo, Zheng; Liu, Wei; Yang, Xiaoyu (Angewandte Chemie International Edition, 2021)
The first kinetic resolution of hydroquinoline derivatives with α,α‐disubstitution has been achieved through asymmetric remote aminations with azodicarboxylates enabled by chiral phosphoric acid catalysis. Mechanistic studies suggest a monomeric catalyst pathway proceeding through rate‐ and enantio‐determining electrophilic attack promoted by a network of attractive non‐covalent interactions between the substrate and catalyst. Facile subsequent removal and transformations of the newly introduced hydrazine moiety enable these protocols to serve as powerful tools for asymmetric synthesis of N‐heterocycles with α,α‐disubstitution. The first kinetic resolution of hydroquinoline derivatives with α,α‐disubstitution was realized through organocatalyzed asymmetric remote aminations with azodicarboxylates, which represents a powerful protocol for asymmetric synthesis of N‐heterocycles with α‐quaternary stereocenters. Mechanistic studies elucidate the reaction mechanisms and highlighted the role of attractive non‐covalent interactions between the substrate and catalyst.